Validity of Deed of Gift That Eliminates Heirs' Rights (Study of Sidoarjo Religious Court Decision No. 3937/Pdt.G/2021/PA.Sda Dated May 18, 2022 - Ritonga, Arifin Syahputra; Purba, Hasim; Barus, Utary Maharany (IHSA Institute, 2024)
This study analyzes the validity of a deed of gift that eliminates the rights of heirs through a study of the Sidoarjo Religious Court Decision No. 3937/Pdt.G/2021/PA.Sda dated May 18, 2022. Using a normative legal research method with an analytical descriptive approach, this study examines three main problems: the position of the deed of gift in relation to the cancellation of the deed due to the loss of heirs' rights, legal protection for the recipient of the gift, and a legal analysis of the Sidoarjo Religious Court Decision No. 3937/Pdt.G/2021/PA.Sda. The results of the study indicate that a deed of gift that eliminates the rights of heirs does not have binding legal force and can be canceled through the Religious Court, legal protection for the recipient of the gift only applies if it does not exceed 1/3 of the assets or obtains the consent of the heirs, and the court decision in this case is considered inappropriate because it cancels 3/4 of the gift even though the recipient of the gift should still be entitled to 1/3 of the part according to the provisions of the Compilation of Islamic Law.